2022
DOI: 10.3390/ijms232012383
|View full text |Cite
|
Sign up to set email alerts
|

The Perspective of Arbuscular Mycorrhizal Symbiosis in Rice Domestication and Breeding

Abstract: In nature, symbiosis with arbuscular mycorrhizal (AM) fungi contributes to sustainable acquisition of phosphorus and other elements in over 80% of plant species; improving interactions with AM symbionts may mitigate some of the environmental problems associated with fertilizer application in grain crops such as rice. Recent developments of high-throughput genome sequencing projects of thousands of rice cultivars and the discovery of the molecular mechanisms underlying AM symbiosis suggest that interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Our study identified significant intraspecific variations in the AM properties of domesticated and wild rice, revealing the enormous potential to improve these properties. Wild rice provides valuable genetic resources for rice breeding (Yu et al, 2021;Huang et al, 2022), and our work suggests the potential of introducing advantageous AM properties from wild rice to their domesticated progeny in future rice breeding programs.…”
Section: Discussionmentioning
confidence: 92%
“…Our study identified significant intraspecific variations in the AM properties of domesticated and wild rice, revealing the enormous potential to improve these properties. Wild rice provides valuable genetic resources for rice breeding (Yu et al, 2021;Huang et al, 2022), and our work suggests the potential of introducing advantageous AM properties from wild rice to their domesticated progeny in future rice breeding programs.…”
Section: Discussionmentioning
confidence: 92%
“…The ecological role of arbuscular mycorrhizal fungi (AMF) in natural ecosystems is a topic of great interest and importance. AMF are symbiotic organisms that form mutualistic associations with the roots of most land plants, facilitating nutrient uptake and enhancing plant growth [1,2]. This relationship has profound implications for the functioning and stability of natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%